Being Gerry Mulligan my life in music - Mulligan, Gerry 1927-1996; Poston, Ken (Backbeat Books, 2023)
"Being Gerry Mulligan: My Life in Music is Gerry Mulligan in his own words. This autobiography tells the story of the iconic American jazz saxophonist, clarinettist, composer, and arranger"--
Keywords: Mulligan, Gerry -- 1927-1996; Geschichte 1927-1996; Jazzmusiker; Saxofonist; USA; Mulligan, Gerry; Jazz musicians / United States / Biography; Saxophonists / United States / Biography; Composers / United States / Biography; Musiciens de jazz / États-Unis / Biographies; Saxophonistes / États-Unis / Biographies; Compositeurs / États-Unis / Biographies; Composers; Jazz musicians; Saxophonists; United States; Autobiography; Autobiographies; Biographies; Autobiografie